ANALYSIS OF VILLAGE FUND MANAGEMENT (Case Study of Suka Negeri Village, Air Nipis District, South Bengkulu Regency) - Widarti Kristiani; Neri Susanti; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
The research objective is to answer the problems that exist in the control of village funds in the village of Suka Negeri, Air Nipis sub district Bengkulu district. Riview and analyze the suitability of village fund management in the village of Suka Negeri, Air Nipis, Bengkulu Sealatan regency based on 2018-2019. Management of village funds in Suka Negeri, Air Nipis sub-district south Bengkulu district in 2018-2019 has met tergets and tergets, village funds in Suka Negeri village are almost 80% right on target, in Suka Negeri village it has a village fund procurement factor, namely the amount of village fund allocation (add) is still limited and yhere is still a lack of intensity in the socialization of village fund so it must be studied in depth.